Seamless Integration of Shunt Active Power Filtering in Fast EV Chargers for Grid Ancillary Services - Ahmed Elottri (22565795) (2025)
This paper presents a novel control strategy for integrating shunt active power filter (SAPF) functionality as an ancillary service in electric vehicle (EV) chargers. The proposed approach employs a bi-directional sliding mode control (BD-SMC) technique to enhance power quality by effectively mitigating harmonics and improving grid stability. The BD-SMC is designed to fulfill the charging requirements including constant current and constant voltage charging modes, in addition to acting as a SAPF when needed. This approach aims to address two critical challenges in modern power systems: mitigating the harmonics introduced by the non-linear loads and enhancing grid stability through the energy storage capabilities of EV batteries. The proposed system enables bi-directional energy flow between the grid and EV batteries, allowing for the batteries to act as both load and storage units. The proposed system is validated through hardware experiments under various scenarios, including steady-state, transient, normal, and abnormal grid voltage condition. Other Information Published in: IEEE Open Journal of Power Electronics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/ojpel.2025.3579781